Growth and yield performance of different open pollinated tomato genotypes in Terai region of Nepal - Tek Prasad Gotame; Surendra Lal Shrestha; Sujata Poudel; Jiban Shrestha (Journal of Agriculture and Natural Resources)
Tomato is one of the major vegetable crops inNepal. The productivity of tomato in Nepal is very low due to lack of high yielding, disease and pests resistant varieties.The objective of the experiement was to evaluate the performance of open pollinated tomato genotypes. Ten open pollinated tomato genotypes were evaluated at on-station research field of Regional Agricultural Research Station, Parwanipur, Bara in the winter seasons of 2015 and 2017, and seven tomato genotypes were evaluated at farmers’ fields of Bara and Parsa districts, Nepal in the winter seasons of 2017 and 2018.The experiments were carried out in randomized complete block design with three replications. Results of the on-station experiments showed that HRDTOM084 produced the highest yield (29.1 t/ha in 2015 and 28.5 t/ha in 2017) and showed consistant performance over the two seasons. It was the superior genotype in terms of yield and yield attributing traits. Tomato genotypes HRDTOM011, HRD109, HRDTOM080 and HRDTOM086 were found vigorous with a score value 5 in 1 to 5 rating scale. The results of the farmers’ field experiment showed that the tomato genotypes HRDTOM084 and HRDTOM085 were found more productive and high yielding compared to other genotypes. The highest yield was produced in HRDTOM084 with a mean of two season yield 49.85 t/ha followed by HRDTOM085 with a mean of two season yield 47.42 t/ha).These genotypes showed moderate resistance to late blight and septoria leaf spot with a score value of 2.3 in 1-5 rating scale. Therefore, HRDTOM084 and HRDTOM085 were the most productive and gave higher yield compared to others. Hence, these two tomato genotypes can be used by tomato growers under field conditions in Terai region of Nepal.